Markov Chain Analysis of Problematic Financing in Sharia Banks - Cahyandari, Rini; Rahmawati, Weni; Saepuloh, Aep (iora, 2024)
Indonesia is the country with the largest Muslim population in the world, which makes people start to switch to sharia banking services because they do not use the usury system. This can be seen from the role of the community in using sharia banking services, including in distributing funds. From financing activities, the more funds distributed, the greater the potential for risk to arise. If there are customers who do not comply with installment payments, this will create a problem in financing in sharia banking, which is called problematic financing. The classification and criteria for problematic financing are divided into three, namely substandard, doubtful and nonperforming. To overcome this risk, preventive measures are taken, one of which is by knowing the possibility of financing problems in the future, which can be calculated using Markov chain analysis. This research uses secondary data on substandard, doubtful and non-performing problematic financing in the period 2016 to 2021 at several sharia banks in Indonesia. The opportunity value is searched until it meets the balance condition (steady state). Based on the research results, it was found that Sharia Commercial Banks (BUS) will experience a state of balance at step 5, Sharia Business Units (UUS) will experience a state of balance at step 11, Sharia Rural Banks (BPRS) will experience a state of balance at step 6.